Incentives and Barriers to Green Building Implementation: The Case of Jakarta - Prasetyawan, Sigid; Machfudiyanto, Rossy Armyn; Rachmawati, Titi Sari Nurul (Journal of the Civil Engineering Forum, 2023)
The low implementation of green building through building certification in Jakarta is responsible for the decreased achievement of reducing greenhouse gas emissions in 2020. This is observed in the energy sector through the efficient use of power in commercial buildings, which is only 37,789 tons (0.72 %) of the 5.26 million tons of CO2e expected in 2030, potentially causing the effects of a climate change-related disaster. In this case, the low prevalence of green buildings is due to the barriers preventing their implementation, with the provision of incentives being a suitable solution regarding its significant influence on rapid development. Therefore, this study aims to determine the influential relationship between barriers, incentives, and the level of green building implementation, to identify the most effective applicable benefits in Jakarta. In this context, path analysis and structural equation modeling (SEM) was used with 101 participants selected from developer/owner institutions, consultants, contractors, and the government experienced in implementing the experimental data of the buildings. These data were subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that cost-risk and knowledge-information barrier significantly impacted the level of green building implementation in Jakarta. This led to the recommendation of non-financial incentives as an effective regional benefit, which relevantly affected the level of green building implementation, as well as cost-risk and knowledge-information barriers. These results were expected to assist policymakers and practitioners in formulating effective incentive policies for the implementation of green buildings in Jakarta.